Are We Ready for the Changes in U.S. Accounting Standards? Some Evidence of Midwestern Universities Curriculum - Kang, Gerui (Grace); Liu, Xiang; Hsiao, Daniel (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2016)
The Financial Accounting Standards Board (FASB) has been working with the International Accounting Standard Board (IASB) on the reformation of the current U.S. accounting standards and the adoption of the concepts of the International Financial Reporting Standards (IFRS) in the U.S. The contents of IFRS have been included in the CPA exam beginning in 2011. The purpose of this study is to investigate whether business schools located in the Midwestern United States are ready for the transition. We find that most of the schools surveyed do not currently offer international accounting course as of spring 2011, either as a required or an elective. We are concerned about whether educators and students in the Midwest are ready for the change. We urge accounting educators to accelerate the integration of IFRS to their accounting curriculum. At the same time, given the resource constraints, it is time for the regulators to seriously consider postponing the deadlines